#TITLE_ALTERNATIVE# - (NIM : 10205007); Pembimbing : Dr. Hendro, NATAL
Determining the thickness and refractive index multiple layer with analysis of attenuated total reflectance curve by curve fitting of Winspall software. Measurement of thickness and refractive index of multilayer can be made by the reflection method. Measurement techniques used in this thesis is to use the method of attenuated total reflectance. By analyzing the attenuated total reflectance curve by curve fitting of Winspall software, the results obtained in the form of magnitude of thickness and refractive index of a multilayer. In this Winspall there is an iterative method that can be used to perform curve fitting of the reflected intensity against incident angle of light, which produces data in form of magnitude of the refractive index and thickness of the layer. Multilayers are used, consist of two layers to six layers. Thickness and refractive index measurements carried out in stages. First step is to find the amount of refractive index prism is used (two-layer system). And then prism coated with a dielectric (a three-layer system), which has been determined the thick and the magnitude of the dielectric refractive index. Having obtained the refractive index in the third layer, then this layering here be covered by other materials (four-layer system), then determined the magnitude of the thickness and refractive index of the fourth layer. The same step has been done until the system had six layers. The results of curve fitting process, which form the refractive index and thickness data had been compared with the literature, such as thickness and refractive index of gold according to the literature a thickness of gold 50 nm and the refractive index 1.10 + 1.5i according to curve fitting a thickness of gold is 45.14 nm and refractive index - 13.3632 + 2.8858i. By analyzing the characteristics of the ATR curve by curve fitting software Winspall the thickness and refractive index multilayer can be known.